2015
DOI: 10.1136/bcr-2015-212032
|View full text |Cite
|
Sign up to set email alerts
|

Stuve-Wiedemann syndrome with a novel mutation

Abstract: We describe a female infant born at term to consanguineous parents, with a suspicion of skeletal dysplasia in utero. At birth, she had short limbs, camptodactyly, dysphagia leading to nasogastric tube feeds, and skeletal survey demonstrating dysplasia of long bones and spine. During infancy, she also developed episodes of respiratory failure necessitating admission to intensive care, and periods of hyperhidrosis managed at home. A basic genetic screen did not reveal any abnormalities. Contact was made with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The third major concern since birth and during infancy are swallowing trouble (74%) which are probably consecutive to pharyngoesophageal dyskinesia due to an abnormal autonomic control [ 23 ]. Nasogastric tube feeding and/or gastrostomy are generally required during infancy to ensure proper feeding and prevent aspiration pneumonia [ 15 , 16 , 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…The third major concern since birth and during infancy are swallowing trouble (74%) which are probably consecutive to pharyngoesophageal dyskinesia due to an abnormal autonomic control [ 23 ]. Nasogastric tube feeding and/or gastrostomy are generally required during infancy to ensure proper feeding and prevent aspiration pneumonia [ 15 , 16 , 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the patient carried the mutation c.144_145dupGG, p. A49Gfs*6 in exon 3 of the LIFR gene homozygously. This mutation had already been described in his sister’s case report 5. This frameshift mutation either results in loss of function of the affected allele due to nonsense mediated decay of the mutant mRNA or in a truncated protein with aberrant or no function.…”
Section: Case Presentationmentioning
confidence: 79%
“…This infant of consanguineous parents was born at term, the mother had three previous miscarriages and two live born children including a daughter diagnosed with SWS 5. Antenatal scans in this pregnancy showed oligohydramnios, short long bones.…”
Section: Case Presentationmentioning
confidence: 92%
“…Many long-term survivors require physical therapy and braces, as well as osteotomies to reduce limb deformities and surgical stabilization of scoliosis ( 8 ). Although motor and growth delay are present, cognitive impairment is not a feature of SWS ( 3 , 4 ). As seen in our case, ocular manifestations are reported to become more prominent, with 45% experiencing corneal ulcers and 48% demonstrating a lack of corneal reflex in patients with SWS after 2 years of age ( 8 ).…”
Section: Discussionmentioning
confidence: 99%